Laparoscopically assisted vaginal hysterectomy vs non-descent vaginal hysterectomy in the benign diseases of the uterus: an interventional study - Mukherjee , Shobha; Singh, Parru; Bedi, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hysterectomy is most common gynaecological surgery done for various indications varying from AUB and fibroid uterus to malignancies. There are various approaches for performing hysterectomy, ranging from laparotomy and laparoscopic to vaginal hysterectomy, in both descent and non-descent cases. Incidence of hysterectomies in India is reported to be low compared to developed countries. Most common indication for hysterectomy being excessive menstrual blood loss due to hormonal reasons or fibroids (size more often not exceeding 12 weeks). Aim of study was to compare intra-op and post-op complications between non-descent vaginal hysterectomy and laparoscopic hysterectomy and establish the better method for hysterectomy in non-descent uterus. Methods: A prospective comparative study of 104 hysterectomies was done over a period of November 2019 to October 2020, with 52 cases each in one group of non-descent vaginal hysterectomy (NDVH) and other group of total laparoscopic hysterectomy LAVH. Demographic characteristics, indications for surgery, operative time, intra-operative blood loss, post-operative analgesia requirements, post-operative hospital stay and post-operative complications were compared between both groups. Results: The most common age in both groups was 41-50 years. Among 104 cases undergoing NDVH and LAVH the most common indication of surgery was Fibroid and DUB. The mean operative time in NDVH group was 90.54±5.89 min while it was 127.12±12.58 min in LAVH group, and the mean blood loss in NDVH group was 108.56±7.14 ml, while it was 89.23±7.37 ml in LAVH group. The intraoperative complication rate in NDVH was more compared to LAVH. Conclusions: The present study concludes that NDVH can be safely offered to patients with benign gynaecological conditions and this scarless approach appears to be the preferred method of hysterectomy. LAVH can be offered as a synergistic surgery in cases where difficulty in operative dissection is anticipated.